Olhares entrecruzados - Guaraldo, Tamara de Souza Brandão; Daniele; Celia; Ugaya, Andresa de Souza (Albuquerque (online), 2021)
The study reports an action research carried out in the city of Bauru/ SP with the agents of the service network for women in situations of domestic and family violence. In order to raise the difficulties in the services provided from a dialogical process, the research provided the production of knowledge aimed at the improvement of services and the reflection of its actors. The results of the different views of the agents of the women’s service network favor mutual training and a perspective of collective change.